Pengaruh Self-Acceptance Terhadap Academic Hardiness pada Mahasiswa Non-Muslim di Kampus Islam - Arief, Yanwar; Hidayat, Ahmad; Munthe, Ricca Angreini; Yusdanisa, Indah (Personifikasi: Jurnal Ilmu Psikologi, 2024)
Non-Muslim students studying at Islamic universities often face challenges, particularly with Islamic studies courses and Muslim dress code ethics. This situation creates a need for academic hardiness, allowing non-Muslim students to endure the academic pressures they encounter in such settings. One factor believed to contribute to the development of academic hardiness is self-acceptance. This research aims to examine the effect of self-acceptance on academic hardiness among non-Muslim students at an Islamic university. The subjects in this study are 104 active non-Muslim students at Universitas Islam Riau. The sampling technique used is nonprobability sampling, specifically snowball sampling. Data was collected using academic hardiness and self-acceptance scales. Data analysis was conducted using Partial Least Squares (PLS) with SmartPLS 3.0 software. The study results show a significant and positive effect of self-acceptance on academic hardiness among non-Muslim students at an Islamic university.